Cognitive Behavioral Intervention for Trauma in Schools (CBITS): A School Social Work Perspective - Karla B Horton PhD, LMSW (International Journal of School Social Work, 2019)
This article reviews research about the effects of traumatic events on the functioning of children and adolescents in a school setting. Interventions with traumatic stressors have been shown to work best when they incorporate multiple elements such as policy change, teacher and administration buy-in, and parent meetings. One intervention, Cognitive Behavioral Intervention for Trauma in Schools (CBITS), has been successfully developed and implemented by school social workers, teachers, and parents to address a range of traumatic stressors. This article will review CBITS training and examine how it could be used to address traumatic stressors in children and adolescents to lower future risk for trauma and adverse outcomes. Implications for the application of trauma-informed practice will be discussed. More specifically, how this training can be adapted to meet the specific needs of a school social worker’s unique environment, considering time constraints, student population, and school administration, faculty and staff.
Keywords: CBITS; trauma-informed practice; counseling; bullying; school social work